A theoretical framework to improve the construct for chronic pain disorders using fibromyalgia as an example. (January 2021) - Kumbhare, Dinesh; Tesio, Luigi
Fibromyalgia (FM) is a frequent, complex condition of chronic musculoskeletal pain with no evidence for biological correlates. For this reason, despite many efforts from the medical community, its construct still appears ill defined. Promising candidate biomarkers are critically reviewed. A research agenda is proposed for developing a clearer construct of FM. The ideal theoretical framework is one of overcoming the illness–disease dichotomy and considering reciprocal interactions between biology and behaviour. This approach may foster research in other fields of pain medicine and of medicine in general.